Weightbearing CT Assessment of Foot and Ankle Joints in Pes Planovalgus Using Distance Mapping. Issue 1 (January 2022) - Bernasconi, Alessio; Netto, Cesar de Cesar; Siegler, Sorin; Jepsen, Maui; Lintz, Francois
Category: Hindfoot; Ankle; Other Introduction/Purpose: The goal of this study was to describe the abnormal joint surface interaction at the ankle, hindfoot and midfoot joints in patients presenting with Pes Planovalgus (PP) using three-dimensional (3D) distance mapping on weightbearing computed tomography (WBCT) images by comparing a series of PPs to a series of normally-aligned feet. We hypothesized that in PPs joint interactions would reveal significantly increased spaces in the medial side of the ankle, hindfoot and midfoot joints. Methods: In this case-control study, ten feet (10 patients) with asymptomatic PP (cases; N=10) were compared to 10 matched- paired (by age, gender and body mass index) normally-aligned feet (10 patients) (controls; N=10). Three-dimensional models were produced from the images and distance maps representing joint surface configuration were generated for the ankle, hindfoot and midfoot joints. The distance maps for each joint were then compared between the two groups and between regions in the same group. Results: In PP patients there was a significantly increased surface-to-surface distance anteromedially at the ankle joint (+46.3%, p<0.001) along with an increased distance on the anterior halves of both the medial (+21.3%, p=0.098) and lateral malleoli (+22.7%, p=0.038). At the posterolateral corner of the posterior facet of the subtalar joint we found an increased surface-to- surface distance (by 57.1%, p< 0.001), while at the talonavicular joint there was a reduction of the distance at the superomedial corner (-20%, p=0.097) along with a significant increase in the upper central (+20%, p=0.039) and lateral (+30.7%, p=0.015) zones. A reduction of the surface-to-surface distance was also observed in three of the four zones of the calcaneocuboid joint. Finally, a statistically significant increase in the mean distance was observed at the naviculocuneiform and tarsometatarsal joints in a range between 38% and 93.4% (p<0.001 in all cases). Conclusion: We found significant differences in surface-to-surface interaction at the foot and ankle joints between Pes Planovalgus and normally-aligned controls. Distance mapping on WBCT images could be used in clinical practice as a diagnostic support to gauge the morphological changes of articular spaces occurring in Pes Planovalgus.